2018
DOI: 10.1038/s41556-018-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

PSPC1 mediates TGF-β1 autocrine signalling and Smad2/3 target switching to promote EMT, stemness and metastasis

Abstract: Activation of metastatic reprogramming is critical for tumour metastasis. However, more detailed knowledge of the underlying mechanism is needed to enable targeted intervention. Here, we show that paraspeckle component 1 (PSPC1), identified in an aberrant 13q12.11 locus, is upregulated and associated with poor survival in patients with cancer. PSPC1 promotes tumorigenesis, epithelial-to-mesenchymal transition (EMT), stemness and metastasis in multiple cell types and in spontaneous mouse cancer models. PSPC1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 63 publications
10
148
0
3
Order By: Relevance
“…A NSCLC cell line, A549 (ATCC ® CCL-185™), was obtained from American Type Culture Collection (ATCC). 27,28 Cells were cultured in the Roswell Park Memorial Institute medium (RPMI 1640, Gibco) with 10% fetal bovine serum (FBS, Gibco), and in a humidified 5% CO 2 incubator at 37°C. The subculture process was performed two times every week.…”
Section: Cell Culturementioning
confidence: 99%
“…A NSCLC cell line, A549 (ATCC ® CCL-185™), was obtained from American Type Culture Collection (ATCC). 27,28 Cells were cultured in the Roswell Park Memorial Institute medium (RPMI 1640, Gibco) with 10% fetal bovine serum (FBS, Gibco), and in a humidified 5% CO 2 incubator at 37°C. The subculture process was performed two times every week.…”
Section: Cell Culturementioning
confidence: 99%
“…(52). Paraspeckle component 1 promote EMT and metastasis through TGF-b sigaling (53). Recently, it was reported that the PI3K-Akt signaling pathway also plays an important role in EMT.…”
Section: Ra Is a Metabolic Intermediate Of Vitamin A And Atramentioning
confidence: 99%
“…We found that 2266 genes are overexpressed in the ADPA tumours, including the crucial oncogenic driver genes KRAS , MDM2 , PDGFA , BCL2L11 , IL6ST , SMAD2 , CCND1 , LEF1 , VEGFA , RAF1 , CDK6 or CDK4 . These genes play essential roles in tumourigenesis and the development of various types of cancer.…”
Section: Discussionmentioning
confidence: 93%